1994
DOI: 10.1002/hep.1840200621
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hepatic ito cell nitric oxide production after acute endotoxemia

Abstract: Nitric oxide is a highly reactive mediator released in the liver by hepatocytes, Kupffer cells and endothelial cells during endotoxin-induced inflammation. In this study we determined whether Ito cells also produce nitric oxide after exposure to endotoxin. For induction of endotoxemia, rats were injected intravenously with Escherichia coli lipopolysaccharide (2.5 mg/kg). Ito cells were isolated from the animals 48 hr later by means of in situ perfusion of the liver with protease and collagenase followed by pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…[14][15][16] Endotoxin, in conjunction with interferon-␥, TNF-␣, and IL-1␤, also stimulates the synthesis of a multifunctional mediator NO in Kupffer cells 17 and hepatocytes. 18 Work from several laboratories, including ours, has demonstrated that endotoxin stimulates synthesis of NO via induction of inducible NO synthase (iNOS), 10,[19][20][21][22] and of TNF-␣ and IL-6 21,22 in both quiescent (normal liver) and activated (fibrotic liver) HSCs. TNF-␣ and IL-6, as well as increased NO (directly or via a potent free radical peroxinitrite), can exert a variety of effects on the hepatic system.…”
mentioning
confidence: 99%
“…[14][15][16] Endotoxin, in conjunction with interferon-␥, TNF-␣, and IL-1␤, also stimulates the synthesis of a multifunctional mediator NO in Kupffer cells 17 and hepatocytes. 18 Work from several laboratories, including ours, has demonstrated that endotoxin stimulates synthesis of NO via induction of inducible NO synthase (iNOS), 10,[19][20][21][22] and of TNF-␣ and IL-6 21,22 in both quiescent (normal liver) and activated (fibrotic liver) HSCs. TNF-␣ and IL-6, as well as increased NO (directly or via a potent free radical peroxinitrite), can exert a variety of effects on the hepatic system.…”
mentioning
confidence: 99%
“…26 As demon-in pathological conditions such as bacterial infections and sepsis that acutely increase NO systematically 1 and in the strated by this study, NO donors stimulated intrahepatic formation and biliary excretion of GSSG, whereas sinusoidal liver. [4][5][6] Chronic increases in NO production are seen in cirrhosis and portal hypertension. 54,55 Bacterial endotoxin, a poand canalicular GSH excretion remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] NO donors, such as sodium nitroprusside (SNP) has not been clearly defined. In the present study, we and S-nitroso-acetyl-penicillamine (SNAP), spontaneously examined the effects of NO on bile flow and biliary release NO in aqueous solution and have been used widely to HCO 0 3 and glutathione excretion in the isolated perfused study NO effects.…”
mentioning
confidence: 99%
“…On the other hand, nitric oxide (NO) is a compound with high oxidation capacity, which is produced from L-arginine amino acid via inducible NO synthase (iNOS) enzyme in hepatocytes and other connective tissue cells in the liver (10)(11)(12)(13)(14)(15)(16)(17). Therefore, it can be suggested that there is a positive correlation between liver damage and increase in NO levels.…”
Section: Background/aims: Tenoxicam Is a Non-steroidal Antiinflammatomentioning
confidence: 99%